A Study on the Relationship between Attachment Styles of School Children Aged 5 â 6 and Personality Traits of Their Mothers - GÃƒÂ¶rgÃƒÂ¼, Ertan; Ural, Ozana (Social Science Learning Education Journal, 2017)
This research aims to investigate the association between attachment styles of school children aged 5-6 and personality traits of their mothers. Designed in accordance with the relational screening model, the study group of the research consisted of 160 mothers and their children (84 girls, 76 boys; 74 five years old, 86 six years old) who agreed to participate in the survey from the districts of EyÃ¼p, BeÅiktaÅ and BeyoÄlu in European side of Istanbul province. The data were collected from 6 different schools. "Personal Information Form" for demographic information, "16 Personality Inventory/Factor (16 PF)" to measure the personality characteristics of the mothers and "Doll Story Completion Test (DSCT)" to measure the attachment styles of the children were used in the research. As a result of the research, a significant relationship was found between the childrens attachment styles and the personality traits of their mothers including extrovert-introvert, anxious-comfortable, realist-sensitive, accepting-independent, free-controlled characters. According to these results, the mothers of securely attached children exhibited statistically significant extrovert, comfortable, sensitive, independent and free personality traits. The findings were discussed in the context of literature on attachment.